Appearance of metastable B2 phase during solidification of Ni50Zr50 alloy: electrostatic levitation and molecular dynamics simulation studies. (4th February 2015) - Quirinale, D G; Rustan, G E; Wilson, S R; Kramer, M J; Goldman, A I; Mendelev, M I
Abstract: High-energy x-ray diffraction measurements of undercooled, electrostatically levitated Ni50 Zr50 liquid droplets were performed. The observed solidification pathway proceeded through the nucleation and growth of the metastable B2 phase, which persisted for several seconds before the rapid appearance of the stable B33 phase. This sequence is shown to be consistent with predictions from classical nucleation theory using data obtained from molecular dynamics (MD) simulations. A plausible mechanism for the B2–B33 transformation is proposed and investigated through further MD simulations.